Synthesis of single crystalline CdS nanocombs and their application in photo-sensitive field emission switches - Chavan, Padmakar G.; Badadhe, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Nanoscale, 2011)
Single crystalline CdS nanocombs were synthesized by a thermal evaporation route. The photo-sensitive field emission current shows a reproducible switching behavior, with a rise in current level of nearly five times the initial preset value of similar to 1 mu A. An ultra low turn-on field, required to draw an emission current density of similar to 0.1 mu A cm(-2) (100 nA), is found to be similar to 0.26 V mu m(-1) (260 V), which is much lower than the reported values for various other CdS nanostructures. Upon illumination with visible light the CdS nanocombs act as a photo field emission switch. At an applied field of similar to 0.65 V mu m(-1) the current densities are observed to be similar to 14.6 mu A cm(-2) and similar to 26.9 mu A cm(-2), without and with light illumination, respectively. The average emission current is seen to be stable over the duration of measurement for two preset values. The high sensitivity and fast response in the visible range indicates that the CdS nanocombs can be used as a photo-sensitive field emitting switch in device applications, and also in pulsed electron beam technology.